Authenticity doubt on the Tomioka (Yishen Lun) manuscript: A discourse analysis - Tam, David (HTS teologiese studies, 2024)
In 1918, Toru Haneda of Tokyo Imperial University published a brief article introducing the Tomioka manuscript as an ancient Chinese Christian (Tang Jingjiao) text titled ‘Yishen Lun 一神論 [Discourse on God]’. He noted that it originated from the Dunhuang Mogao Grotto and was acquired by Tomioka Kenzo through a bookseller in 1917. In subsequent publications, Haneda dated the manuscript to 641 CE and published the complete text. In 1930s, P.Y. Saeki translated the text into English and affirmed the manuscript’s authenticity. In his 2000 and 2005 articles, Lin Wushu raised questions about the manuscript’s authenticity, doubts that Rong Xinjiang echoed in a 2014 book chapter. Rong further recommended that the Tomioka manuscript be excluded from the Jingjiao corpus. These articles launched the authenticity doubt on the Tomioka manuscript and have since become central to the discussion of this issue. This article applies James L. Kinneavy’s discourse theory to analyse the nature and robustness of Lin and Rong’s arguments. While confirming or denying the authenticity of the manuscript is outside the scope of this article, it aims to shed light on the issues as raised and argued within Ling and Rong’s articles. The analysis concludes that Lin’s approach is primarily exploratory, but it lacks strong initial probabilities to advance the discourse to a more formal (or scientific) level. On the other hand, Rong attempted a scientific approach using deductive reasoning; but even if the facts he used are valid, they do not logically support the conclusion that the Tomioka manuscript is a forged ‘Aluoben document’. Furthermore, the article underscores the fact that the concept of ‘forging an Aluoben document’ is inherently problematic, as the notion of an ‘Aluoben document’ did not exist at the time of the alleged forgery.Contribution: The Tomioka manuscript, praised in Jingjiao scholarship for its originality and theological breadth and depth, and comprising half of the entire Jingjiao corpus, faces dismissal because of authenticity doubts. This article argues that the case for forgery is neither well-established nor proven, making the proposal for exclusion premature.